O sistema deliberativo da política de assistência social no contexto da ascens\~ao de novos projetos políticos no governo federal - Marina Brito Pinheiro; Denise do Carmo Direito (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Former president Jair Bolsonaro put into words the political project that prevailed during his government, which can be translate as a liberal-conservative-authoritarian perspective. This article seeks to understand if and how this political project changed routines, considering consolidated practices arising from previous participatory political projects. In this study, we focus on the complex participatory systems of the social assistance policy, particularly at the national level - the national council and conferences, as well as the intergovernmental commission -, due to the relevance that these forums have for the implementation and structuring of this policy. The analytical framework of the study is based in categories proposed by Charles Tilly (2013) to analyze democratization/de-democratization processes: breadth, equality, protection, and mutually binding nature of consultations. To keep track with the changes that took place in that period, we added to that framework two additional categories: the formal and informal dimension of the shifts, as well as the covid pandemic as a relevant player in the entire process. The conclusion points out that despite not being able to change formal rules that formatted the participation system, it was possible to identify a process of de-democratization, with relative losses in participation mechanisms and federative coordination during the government under analysis.
Keywords: Z18; I39; 330; Social participation; political projects; de-democratization